Goodbye Electronic Health Record?...European Federation for Medical Informatics (EFMI) Special Topic Conference (STC), September 7–8, 2022, Cardiff, Wales. - HAMMOND, W. Ed; BENT, Brinnae; WEST, Vivian L. (Studies in Health Technology & Informatics, 2022)
The Electronic Health Record has failed to meet its intended purpose. We propose a new approach focusing on the use of data for health and health care. The first step is to create a repository of all patient data with data storage independent of data use. All use functionality is external to data storage. We propose the development of a common data model in which data elements have a rich set of attributes including actionable knowledge. Finally, functionality is provided through a series of application program interfaces (API). New APIs will address directly new methods for using data to increase the effectiveness of data application to improve management of the health and care of a patient. Together these components will open a pathway to finally accomplish the goals of a better future health system.